Pemilihan Moda Transportasi Pematangsiantar menuju Bandara Silangit Dengan Metode Stated Preference - SITINJAK, Laskar Laurensius; SITINDAON, Charles (Jurnal Rekayasa Konstruksi Mekanika Sipil, 2019)
This study aims to understand user’s mode choice preference between bus and private car in making trip from Pematangsiantar to Silangit Airport. We collected responses from 188 respondents who make the trip between aforementioned route. Majority (36% and 41%) states that tariff is the reason to choose bus, and convenience for private cars respectively. The utility function for choosing bus over car is: (Ubus–car) = 0.127 - 0.042X1 - 0.012X2 - 0.019X3 + 0.072X4 + 0.282X5; where: X1 = difference in cost, X2 = time difference, X3 = headway difference, X4 = service difference and X5 = difference in frequency. This study finds that users mode choice preference is sensitive to the difference in service and frequency. The increase in these two attributes improves probability in choosing bus. Further, the probability of choosing bus is still high if there is no change in cost, time, headway difference of the current condition.